FEATURES OF LEXICAL-SEMANTIC USE OF THE TERMS “GRANDFATHER AND GRANDMOTHER” IN THE UZBEK LANGUAGE - Akhtamova Nigora Bakhtiyorovna (International Journal of Literature and Language Studies, 2026)
In this article, we will consider the features of lexical-semantic use of the terms “grandfather” and “grandmother” in the Uzbek language. These terms are inextricably linked with the social life, culture and traditional values ​​of the people, and their semantic content not only expresses old age and intergenerational relations, but also serves to highlight the national characteristics of the language. It is also shown what semantic meanings the terms “grandfather” and “grandmother” have in folk oral literature, literary texts and everyday speech.